Manajemen Rantai Pasok Usaha Agroindustri Keripik Keladi (Xanthosoma sagittifolium) Pada UMKM Malk Chips - Roswandy, Natasya; Timisela, Natelda R; Tuhumury, Maisie T. F. (AGRICA, 2024)
This research aims to Determine and Analyze the Supply Chain as well as the Efficiency and Performance of the Supply Chain in Malk Chips SMEs. The research method used is Purposive Sampling to determine samples based on suitability of criteria or characteristics of the Malk Chips’s Taro Chips Agro-Industry Supply Chain Mechanism, Marketing Margin Analysis, Farmer's Share Analysis, and SCOR Analysis. The research results show that the Supply Chain members of Malk Chips SMEs consist of Suppliers, Producers, Distributors and Consumers. Based on the results of SCOR Analysis, the Supply Chain Performance Value for Malk Chips SMEs is 45,707. The highest Farmer's Share value is in Channel II which has an efficiency value of 100% for both 200gr and 350gr chips, while Channel I have an efficiency value of 78,78 % for 200gr taro chips and 87,5% for 350gr Taro Chips.